2018
DOI: 10.1111/nph.15137
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated diversification is related to life history and locomotion in a hyperdiverse lineage of microbial eukaryotes (Diatoms, Bacillariophyta)

Abstract: Summary Patterns of species richness are commonly linked to life history strategies. In diatoms, an exceptionally diverse lineage of photosynthetic heterokonts important for global photosynthesis and burial of atmospheric carbon, lineages with different locomotory and reproductive traits differ dramatically in species richness, but any potential association between life history strategy and diversification has not been tested in a phylogenetic framework.We constructed a time‐calibrated, 11‐gene, 1151‐taxon phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 80 publications
13
110
1
1
Order By: Relevance
“…The relatively high global extinction fraction ( ε = 0.8; Table ), estimated here from extant species only, was similar to calculations made from Cenozoic marine fossils (ε = 0.75; Nakov et al. ). Analyses using alternative implementations of the conditioning of survival of crown lineages indicated that the two approaches produce very similar results (Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The relatively high global extinction fraction ( ε = 0.8; Table ), estimated here from extant species only, was similar to calculations made from Cenozoic marine fossils (ε = 0.75; Nakov et al. ). Analyses using alternative implementations of the conditioning of survival of crown lineages indicated that the two approaches produce very similar results (Fig.…”
Section: Resultssupporting
confidence: 84%
“…For example, the net diversification waiting time for marine planktonic lineages under the MuHiSSE model was 17 My in first and 2.7 My in the second hidden state, whereas the waiting time for oogamous nonmotile diatoms (most common in the marine plankton) was previously estimated as between 16.6 and 100 My (phylogenetic data) or roughly 34.5 My (fossil data) (Nakov et al. ). The relatively high global extinction fraction ( ε = 0.8; Table ), estimated here from extant species only, was similar to calculations made from Cenozoic marine fossils (ε = 0.75; Nakov et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to constraints of our dataset, we were not able to reliably make inferences using hiSSE or fiSSE analyses (see ). Finally, to summarize diversification rates over time and with respect to each character state, we adopted the approach of Nakov, Beaulieu, and Alverson (): we binned the phylogeny into time‐intervals of 0.001 units, resampled the parameter estimates at each interval and then plotted the values by character state. Note that diversification rates are sensitive to the maximum tree depth and are inflated due to the relative time calibration in BEAST (); however, this should not affect conclusions drawn within the clade.…”
Section: Methodsmentioning
confidence: 99%